Simulation of an active front bumper system for frontal impact protection - Nur Rashid, Mat Nuri @ Md Din; Alif Zulfakar, Pokaad; Khisbullah Hudha, Dr.; Mohd Zakaria, Mohd Nasir (Universiti Malaysia Pahang (UMP), 2010)
MUCEET 2009 is organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussein Onn (UTHM), Universiti Teknikal Melaka (UTeM) and Universiti Malaysia Pahang (UMP), 20th - 22nd June 2009 at M. S. Garden Hotel, Kuantan, Pahang.